On the issue of effectiveness of the oil production electrical equipment repairs management with a strategy for technical condition - V. M. Levin; N. P. Guzhov; D. A. Boyarova (Известия высших учебных заведений: Проблемы энергетики)
PURPOSE. To consider aspects of solving the complex problem of reasonable choice and assignment of the repair management strategy for the equipment of power supply systems of oil production consumers according to the actual technical condition. To form a methodology for assessing the comparative effectiveness of repair management strategies: «By frequency, running hours» and «By technical condition». To verify the performance of the integrated methodology. Justify and demonstrate the effectiveness of the repair management strategy: «By technical condition» of the equipment on the real example of the typical scheme of the electrical supply system of oil fields.METHODS. In solving the problems set: the method of block diagrams for calculating the structural reliability of electric distribution network, including the probabilities of power supply failure in the circuit of each technological consumer, taking into account the possibility of redundancy and imposing an emergency restoration of the main element on the planned repair of the reserve, the method of hierarchy analysis for integral assessment of the actual technical condition of electrical equipment 6 (10) kV, method of calculating the mathematical expectation of damage from technological losses of oil production to assess the severity of the consequences of disruption of electricity supply to consumers of oil production, the method of expert decisions to adjust the regulatory periodicity and frequency of scheduled repairs of equipment, depending on the actual value of technical condition index.RESULTS. The relevance of the research direction is substantiated. Computational methodology of comprehensive assessment of comparative efficiency of equipment repair management strategies in oilfield power supply system «By frequency, running hours» and «By technical condition» to justify the priority of one of them has been formed. On a concrete computational example the preference of strategy choice «By technical condition» is proved as applied to the equipment of 6(10) kV power supply systems of oil fields.CONCLUSION. The developed methodology and its validation on the example of a real power supply system allows to substantiate and illustrate the effectiveness of the strategy «By technical condition» in comparison with the strategy: «By frequency, running hours» in relation to the management of repairs of oil production facilities.